Iceland : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Iceland. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights Iceland's continued real GDP growth, driven by tourism. Growth reached 7.2 percent in 2016 and is projected at almost 6 percent in 2017 before tapering to about 2.5 percent over the medium term. Bank credit to the nonfinancial private sector remains muted, growing only 4.3 percent in 2016, but it is expected to pick up. Thus far, growth has been driven not by leverage but by exports, private consumption, and investment. Iceland's current account surplus is projected to shrink modestly over time, with some export sectors suffering while others thrive.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet